Silver quasi-nanoparticles: bridging the gap between molecule-like clusters and plasmonic nanoparticles. Issue 16 (27th July 2021) - Douma, Fatima; Lakiss, Louwanda; Lebedev, Oleg I.; Cardin, Julien; Kostov, Krassimir L.; El Fallah, Jaafar; Valtchev, Valentin; El-Roz, Mohamad
Abstract : Herein, we report a new strategy for preparing connected silver sub-nanoparticles with unique optical behavior via the selective photo-assisted electrochemical reduction of silver cations in FAU-type zeolite X (FAUX) cages. Abstract : Herein, we report a new strategy for preparing connected silver sub-nanoparticles with unique optical behavior via the selective photo-assisted electrochemical reduction of silver cations in FAU-type zeolite X (FAUX) cages. Bi 2+ /Bi 3+ -doped zeolite nanoparticles (ZX-Bi) were prepared by one-pot hydrothermal synthesis and stabilized as a colloidal water suspension. A ZX-Bi suspension, containing silver nitrate, was subjected to UV irradiation resulting in the reduction of silver cations and the generation of Ag n &+ (with n > &) clusters (Ag@ZX-Bi). The physicochemical characterization of the samples, using XRD, TG, N2 sorption, NMR, HRTEM-STEM, ICP, EDX and XPS analyses, provided comprehensive information on the textural and structural properties, the chemical compositions and the metal oxidation states of the samples. Their optical behavior was investigated using UV-visible and photoluminescence spectroscopies. The IR- operando analysis under visible-light revealed local heating of Ag@ZX-Bi up to 400 K. Theoretical calculation of the absorption, scattering, and extinction cross-sections, σ abs, σ sca and σ ext, respectively, of the different silver models prepared in this study was in agreement with the experimental data, elucidating the unique optical behavior of the silver particles. The set of analyses shows that quasi-nanoparticles of Ag are formed from bridged Ag clusters (AgCLs) through zeolite channels closing the gap between clusters and plasmonic nanoparticles for the first time.